The Aspects of Conflict in the Poetry in Fadwa Tuqan’s Poet - Al-Sarraj, Imad Muhammad Tawfiq Zaidan (Journal of Ecohumanism, 2025)
Fadwa Tuqan, a Palestinian poet born in Nablus in 1917 and deceased in 2003, is recognized as one of the foremost voices in modern Arabic literature. As the seventh of ten children in her family, she experienced a childhood characterized by oppression and rejection, deprived of parental affection, a theme she articulated in her autobiography, "Mountainous Journey." Her birth was unwelcome; her mother had attempted to terminate the pregnancy, and Fadwa only learned of her birthdate through the death of a cousin during her mother’s seventh month of pregnancy. Following her birth, her care was entrusted to a housemaid, who imposed strict limitations, such as forbidding her from playing with dolls at the age of eight. Fadwa's upbringing was dominated by rigid societal traditions and patriarchal control. After the death of her brother Ibrahim, her father encouraged her to compose political poetry to fill the void left by his absence. Nevertheless, she began writing patriotic poetry of her own accord, driven by internal conviction rather than external pressure. A significant transformation in her literary trajectory occurred after the Naksa (the 1967 Arab Israeli War). This period marked her transition from introspective romanticism to a realist engagement with Palestinian political and social realities. Her works became deeply rooted in the Palestinian cause, reflecting her dedication to her homeland and its people through both poetry and prose.